MODEL KELEMBAGAAN PENELUSURAN PASOKAN BAHAN BAKU INDUSTRI GELATIN DARI KULIT SAPI - Syarifuddin Nur; Gumbira Said; Jono Munandar; Machfud Machfud (Universitas Sebelas Maret, 2010)
In the provision of product for halal quality, there were several criterias that must be met in terms of the types of materials or substances (material), the procedure of preparation and how to get it. Products that was studied were cattle hides, but these products were not automatically considered as halal products, without a tracking process and standardization using applied halal standard, even though the origin of these raw material of products do not infringe the requirements of halal. To perform a traceability gelatin raw materials, a system was needed which allows the user to obtain information about the origin of raw materials and the quality process at every stage to the finished · products effectively. Tracking system (traceability system) involved several parties, who have different needs and goals in the process of providing raw materials. Therefore institutional systems engineering was needed to manage the tracking process and bridge the procurement of gelatine raw materials, in order to guarantee the quality of products. It can be used to facilitate the industry and users to create a gelatine standard quality such as standardization of halal quality. The purpose of this study was to formulate the institutional tracking model of raw material for gelatin industrial from cattle hide based on various criteria and assessment of experts. The method used in this study were Interpretative Structural Madding (ISM) to formulate an institutional tracking model of raw material for gelatine industrial from cattle hide efficiently, Analytical Hirarchy Process (AHP) to select the traceability strategy of raw materials for gelatine industrial from cattle hide, and Data Envelopment Analysis (DEA). to analyze optimal performance of the selected model. The results of this study was key elements of institutional tracking system of raw material for gelatine industrial from cattle hide that most influent in the development of gelatine industry and tracking strategies of raw material for gelatin industrial from cattle hide in Indonesia, as well as the optimal model to implement the strategies.